2018
DOI: 10.1002/adom.201800667
|View full text |Cite
|
Sign up to set email alerts
|

Optical Energy Losses in Organic–Inorganic Hybrid Perovskite Light‐Emitting Diodes

Abstract: easily tunable band gaps. [4][5][6][7] LEDs based on such materials have been attracting increasing attention since the first roomtemperature perovskite LEDs (PeLED) developed in 2014. [13] The development of PeLEDs has progressed very rapidly, realizing a record-high external quantum efficiency (EQE) of 11.7% in 2016. [14] Similar to other LED categories, e.g., organic LEDs (OLEDs) [15] and quantumdot [16,17] LEDs, the EQE of PeLEDs is determined by the internal quantum efficiency (IQE) and light out-coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 54 publications
1
99
0
Order By: Relevance
“…Numerous strategies to improve the EQE of PeLEDs are being actively pursued in order to bring their performance in line with other, more established, LED technologies . However, a disparity of refractive index ( n ) between organic transport layers (typically in the range of 1.6–1.8) and the perovskite emissive layer (≈2.3 near the emission wavelength) holds back performance . Due to the high n of the perovskite layer, the maximum EQE of PeLEDs is limited by outcoupling efficiency and restricted to ≈20%, with the remainder of light being trapped within the thin film and substrate materials, as well as parasitic absorption .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous strategies to improve the EQE of PeLEDs are being actively pursued in order to bring their performance in line with other, more established, LED technologies . However, a disparity of refractive index ( n ) between organic transport layers (typically in the range of 1.6–1.8) and the perovskite emissive layer (≈2.3 near the emission wavelength) holds back performance . Due to the high n of the perovskite layer, the maximum EQE of PeLEDs is limited by outcoupling efficiency and restricted to ≈20%, with the remainder of light being trapped within the thin film and substrate materials, as well as parasitic absorption .…”
mentioning
confidence: 99%
“…However, a disparity of refractive index ( n ) between organic transport layers (typically in the range of 1.6–1.8) and the perovskite emissive layer (≈2.3 near the emission wavelength) holds back performance . Due to the high n of the perovskite layer, the maximum EQE of PeLEDs is limited by outcoupling efficiency and restricted to ≈20%, with the remainder of light being trapped within the thin film and substrate materials, as well as parasitic absorption . Therefore, it is necessary to investigate alternative device architectures that are able to enhance outcoupling efficiency and realize direct benefits to EQE.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research is done in the field of organic LEDs (OLEDs) by incorporating molecules that show thermally activated delayed fluorescence and by exploiting charge‐transfer (CT) states that either emit light or serve as a host system . Besides that, new materials like quantum dots or perovskites are heavily investigated . One major drawback is that in most of the aforementioned fields the device stack design is still mainly done by trial and error, e.g., by testing several material combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Even though numerous studies have been carried out on the use of perovskite structures in light-emitting diodes, the study of the electroluminescence properties of these structures, without the aid of electron and hole transmitter layers, is done, for the first time, in this study. This is due to the higher mobility of charge carriers in perovskite structures [19][20][21][22][23][24]. It has been shown that by sandwiching a perovskite layer between the organic hole layer and the electron blocking layer in perovskite-based light-emitting diodes, a narrow emission spectrum and a high quantum yield can be obtained [25].…”
Section: Introductionmentioning
confidence: 99%